Etika Komunikasi Bisnis dalam Perspektif Islam - Nita Andriani (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2021)
The business world in the future is faced with intense competition, companies that have mature management will be superior and can last a long time. Basically, for Muslims when doing business, it is not only to get abundant profit. But also get blessings for every transaction that exists. Therefore it is necessary to have ethics in communicating in business. Which ethics is a reflection of the integrity of business people in determining attitudes and behavior to interact with others. This research approach uses research methods to obtain data used by means of observation or looking for direct references and also secondary data related to Islamic business communication. The results of this study are: morality used as a guideline for communication ethics, namely (1) Fairness (honesty) (2) Accuracy (accuracy of information); (3) free and responsible; (4) constructive criticism; (5) Fair and impartial; (6) Does not like badmouthing (Ghibah); (7) Do not like prejudice (Su'uzh-zhann, When ethics and communication are implemented in business relationships, it can be concluded that Islamic communication ethics is a method of communicating in accordance with moral values â€‹â€‹in judging right or wrong based on the behavior of business people. where every transaction that exists must contain divine elements (Ø§Ù„Ù‡ÙŠ), both in the form of a human relationship with Allah ï·» and humans (ØØ¨Ù„ Ù…Ù† Ø§Ù„Ù„Ù‡) as well as Humans and Humans themselves (ØØ¨Ù„ Ù…Ù† Ø§Ù„Ù†Ø§Ø³), thus directing humans to the benefit of the world and the hereafter.